2010
DOI: 10.1097/aud.0b013e3181e627e7
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Temporal Fine Structure as a Function of Age

Abstract: Objectives-The purpose of this study was to determine whether the processing of temporal fine structure diminishes with age, even in the presence of relatively normal audiometric hearing. Temporal fine structure processing was assessed by measuring the discrimination of inter-aural phase differences (IPDs). The hypothesis was that IPD discrimination is more acute in middle-aged observers than in older observers but that acuity in middle-aged observers is nevertheless poorer than in young adults.Design-Two expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
174
4
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(204 citation statements)
references
References 32 publications
23
174
4
3
Order By: Relevance
“…Scores on the TFS-LF task were not significantly correlated with absolute thresholds at the test frequency. These results confirm those of Ross et al (2007) and Grose and Mamo (2010), and indicate that the decline in sensitivity to binaural TFS with increasing age is already apparent by middle age. Füllgrabe et al (2015) used the TFS-LF task with their young and older groups with matched (normal) audiograms, as described above.…”
Section: Binaural Processing Of Tfssupporting
confidence: 80%
“…Scores on the TFS-LF task were not significantly correlated with absolute thresholds at the test frequency. These results confirm those of Ross et al (2007) and Grose and Mamo (2010), and indicate that the decline in sensitivity to binaural TFS with increasing age is already apparent by middle age. Füllgrabe et al (2015) used the TFS-LF task with their young and older groups with matched (normal) audiograms, as described above.…”
Section: Binaural Processing Of Tfssupporting
confidence: 80%
“…While we hypothesized that we would see such differences, we expected them to correlate with age, reflecting degradations in the fidelity with which the sensory system encodes fine temporal details even in pre-senescent (middle-aged) listeners. This expectation was driven by previous studies of middle-aged listeners that reveal deficits in physiological responses evoked by changes in interaural cues (Ross et al 2007;Ross 2008;Wambacq et al 2009), as well as psychophysical studies that reveal deficits in performance by middle-aged listeners (Grose et al 2006;Helfer and Vargo 2009;Grose and Mamo 2010). Despite this, on our task, we found that age did not predict individual differences in performance.…”
Section: Discussioncontrasting
confidence: 52%
“…Anecdotally, even middle-aged listeners report problems with selective auditory attention (Helfer and Freyman 2008;Wambacq et al 2009). A recent study shows that interaural phase discrimination is poorer in middle-aged listeners (40-55 years) than in young listeners (18-27 years; it is poorer still in older listeners aged 63-75), suggesting that temporal fine structure processing degrades at an earlier age than is often assumed for other forms of presbycusis (Grose and Mamo 2010). Other recent studies also show that middle-aged listeners perform worse than younger listeners in some tasks, particularly those involving temporal processing (Grose et al 2009;Helfer and Vargo 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that both hearing loss and age can adversely affect the processing of TFS information Moore 2007, 2011;Grose and Mamo 2010;Moore et al 2012, Moore, Vickers, andMehta 2012;Füllgrabe 2013;Füllgrabe and Moore 2014;Füllgrabe, Moore, and Stone 2015). This has led to interest in the development of tests that could be used in the clinic or in large-scale research studies to assess monaural and binaural sensitivity to TFS.…”
Section: Introductionmentioning
confidence: 99%